Computational fluid dynamic modelling of NOx formation in diesel engine - S. S., Hoseini; G., Najafi; B., Ghobadian; H., Azimi-Nejadian; Hossein, Ahmadian (IOP Publishing, 2020)
The purpose of this study is offering a numerical model to predict the NOx formation of a diesel engine. For this purpose, simulation of combustion and emissions of a diesel engine was performed using CFD FIRE commercial software. The simulation was performed for the condition of 900 rpm for engine speed, 200 bar cylinder pressure, and injection timing (15° CA BTDC). The difference between the experimental and numerical results was reported by about 3.2%. The result of the numerical simulation shown due to the non-homogeneous mixture of air and fuel in a diesel engine, the temperature distribution is not uniform and the temperature in some places reaches 2500 K. In areas with an equilibrium ratio (stoichiometry) and temperatures above 2000 K, nitrogen oxide is the highest. Also, the result shown areas with a temperature range between 1500 and 1900 K are more favorable areas for the formation of soot pollutant.